Triple-shelled NiMn2O4 hollow spheres as an efficient catalyst for low-temperature selective catalytic reduction of NOx with NH3. Issue 70 (14th August 2018) - Han, Yanling; Mu, Jincheng; Li, Xinyong; Gao, Jinsuo; Fan, Shiying; Tan, Feng; Zhao, Qidong
Abstract : Unique triple-shelled NiMn2 O4 hollow spheres are fabricated by a facile solvothermal method. Abstract : Unique triple-shelled NiMn2 O4 hollow spheres are fabricated by a facile solvothermal method. Owing to its particular triple shell structure, the as prepared NiMn2 O4 catalyst exhibits superior low-temperature NH3 -SCR catalytic performance, achieving above 90% NO x conversion in the temperature range from 100 °C to 225 °C.